2019
DOI: 10.1027/1618-3169/a000466
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Money Priming on Self-Focus in the Imitation-Inhibition Task

Abstract: Abstract. The self-sufficiency hypothesis suggests that priming individuals with money makes them focus more strongly on themselves than on others. However, recently, research supporting this claim has been heavily criticized and some attempts to replicate have failed. A reason for the inconsistent findings in the field may lay in the common use of explicit measures, because they tend to rely on one or just a few items and are thus prone to demand effects and low reliability. In the present research, we admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 82 publications
2
16
0
Order By: Relevance
“…This gave us 80% power to detect an effect size of dz = 0.57 with an alpha error probability of α = .05 (two-tailed). This effect size roughly corresponds to a recent meta-analysis on the influence of social moderators on automatic imitation (Genschow, Schuler, et al, 2019), which yielded an effect size of dz = 0.58. Participants' age ranged from 18 to 25 (M = 18.88; SD = 1.56).…”
Section: Methodssupporting
confidence: 82%
“…This gave us 80% power to detect an effect size of dz = 0.57 with an alpha error probability of α = .05 (two-tailed). This effect size roughly corresponds to a recent meta-analysis on the influence of social moderators on automatic imitation (Genschow, Schuler, et al, 2019), which yielded an effect size of dz = 0.58. Participants' age ranged from 18 to 25 (M = 18.88; SD = 1.56).…”
Section: Methodssupporting
confidence: 82%
“…As a counter-point, however, it should be noted that a small but increasing number of studies have used more robust methods (e.g., larger sample sizes, multiple experiments, pre-registration) and show evidence for social modulation (e.g., Genschow et al, 2020). Such studies are an encouraging sign for the field, although they stop short of providing evidence that the effects rely on a social or specialised mechanism.…”
Section: Theoretical and Methodological Reform Is Requiredmentioning
confidence: 99%
“…Previous research has shown that a focus on the self (relative to others) reduces automatic imitation Genschow, Schuler, et al, 2019;Hogeveen & Obhi, 2011;Leighton et al, 2010;Spengler et al, 2010;van Baaren et al, 2003;Wang & Hamilton, 2013). Based on this finding, Spengler et al (2010) speculated that belief in free will "might help counteract predominant imitation-driven behavior" (p. 105).…”
Section: Potential Reasons For the Null Findingmentioning
confidence: 97%